Emotional Intelligence and Decision Making - A M Kustubayeva; E V Bagayeva (Peoples' Friendship University of Russia (RUDN University), 2011)
The results of the experimental research of the connection between the efficiency of decision making and emotional intelligence are presented in the article. The empirical data indicate that the ability to regulate emotion is an important indicator of the efficiency of decision making in the conditions of psychological experiment.